The Takharrūj Method as an Islamic Legal Solution for Customary Inheritance Practices among Muslim Communities in Pakamban Laok, Sumenep, Indonesia - Takdir, Mohammad; Munir, Fajrul; Ludhfi, Ali; Muliyanzah, Muliyanzah; Muttaqin, Zainol (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
The division of inheritance that does not comply with Islamic law can instigate family conflicts. This assumption is contradicted by what occurs in Muslim society in Pakamban Laok Village, Sumenep Regency, Indonesia, where they can control conflicts by dividing the inheritance under customary law. This article examines why Muslim communities do not apply Islamic inheritance law and how their inheritance division practices can mitigate family conflicts. The study employs a case study approach with data collected through observation, interviews, and documentation. The study found that education, religiosity, economics, and social factors contribute to why the Muslim community in Pakamban Laok does not divide the inheritance of heirs under Islamic inheritance law. Testators typically divide their inheritance (gifts or hibah) to prevent family conflicts before passing away. If the inheritance has not been divided, it is distributed by the heirs, with the shares adjusted by agreement. In some cases, the heirs have invited a local religious scholar to divide the inheritance according to Islamic law, and some other heirs have opposed the division’s results. In Islamic jurisprudence, dividing inheritance to prevent family conflicts is called “takharrūj,” selling a share in inheritance. The authors argue that the takharrūj model can be used as a legal solution for inheritance division practices that are customary and familial.